Long‐term trajectories of self‐reported cognitive function in a cohort of older survivors of breast cancer: CALGB 369901 (Alliance). Issue 22 (22nd July 2016) - Mandelblatt, Jeanne S.; Clapp, Jonathan D.; Luta, Gheorghe; Faul, Leigh Anne; Tallarico, Michelle D.; McClendon, Trina D.; Whitley, Jessica A.; Cai, Ling; Ahles, Tim A.; Stern, Robert A.; Jacobsen, Paul B.; Small, Brent J.; et al.
Abstract : BACKGROUND: The number of survivors of breast cancer aged ≥65 years ("older") is growing, but to the authors' knowledge, little is known regarding the cognitive outcomes of these individuals. METHODS: A cohort of cognitively intact older survivors with nonmetastatic, invasive breast cancer was recruited from 78 sites from 2004 through 2011; approximately 83.7% of the survivors (1280 survivors) completed baseline assessments. Follow‐up data were collected at 6 months and annually for up to 7 years (median, 4.1 years). Cognitive function was self‐reported using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ‐C30); scores ranged from 0 to 100, with a higher score indicating better function. Group‐based trajectory modeling determined trajectories; women were assigned to a trajectory group based on the highest predicted probability of membership. Multinomial logistic regression evaluated the association between receipt of chemotherapy (with or without hormonal treatment) and trajectory group. RESULTS: Survivors were aged 65 to 91 years; approximately 41% received chemotherapy. There were 3 cognitive trajectories: "maintained high" (42.3% of survivors); "phase shift" (50.1% of survivors), with scores slightly below but parallel to maintained high; and "accelerated decline" (7.6% of survivors), with the lowest baseline scores and greatest decline (from 71.7 [standard deviation, 19.8] to 58.3 [standard deviation, 21.9]). The adjusted odds of being in the accelerated decline group (vs the maintained high group) were 2.1 times higher (95% confidence interval, 1.3‐3.5) for survivors who received chemotherapy (with or without hormonal therapy) versus those treated with hormonal therapy alone. Greater comorbidity and frailty also were found to be associated with accelerated decline. CONCLUSIONS: Trajectory group analysis demonstrated that the majority of older survivors maintained good long‐term self‐reported cognitive function, and that only a small subset who were exposed to chemotherapy manifested accelerated cognitive decline. Future research is needed to determine factors that place some older survivors at risk of experiencing cognitive decline. Cancer 2016;122:3555–3563 . © 2016 American Cancer Society Abstract : Among older survivors of breast cancer who were followed for up to 7 years, approximately 42% reported maintaining high cognitive function, but receipt of chemotherapy (with or without hormonal therapy) appeared to double the odds of being in the group that reported accelerated cognitive decline (vs maintaining high function), compared with receiving hormonal treatment alone. Further research is needed to determine factors that place some older survivors at risk of experiencing cognitive decline.